2022
DOI: 10.1186/s12905-022-01974-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between exposure to family planning messages on different mass media channels and the utilization of modern contraceptives among young women in Sierra Leone: insights from the 2019 Sierra Leone Demographic Health Survey

Abstract: Background: Access to sexual and reproductive health information enables young women to make appropriate decisions. We examined the association between exposure to family panning messages on different mass media and the use of modern contraceptives among young women in Sierra Leone.Methods: This was a secondary analysis of the 2019 Sierra Leone Demographic and Health Survey data of young women aged 15-24 years. Multistage stratified sampling was used to select study participants in the survey. We used multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 51 publications
(62 reference statements)
5
10
1
Order By: Relevance
“…Furthermore, in contrast with most studies (11,29,37) our findings showed exposure to family planning messages was not significantly associated with the use of contraceptives. This may be connected with the low exposure to family planning messages among the women.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in contrast with most studies (11,29,37) our findings showed exposure to family planning messages was not significantly associated with the use of contraceptives. This may be connected with the low exposure to family planning messages among the women.…”
Section: Discussioncontrasting
confidence: 99%
“…Besides, studies (23)(24)(25)(26)(27)(28)(29) have also explored the association between exposure to family planning (FP) messages and use of modern contraceptives. Evidence from these studies suggest exposure to FP messages via different conventional and social media channels, was associated with a higher likelihood of modern contraceptive use.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the media is immense in raising awareness and knowledge of contraceptive use, and even dispelling misinformation about family methods [ 33 35 ]. The study showed significant association between media exposure and the use of modern contraception methods.…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence on the efficacy of radio programs on the knowledge and uptake in Ethiopia and SSA is limited, evidence from sub-Saharan Africa suggests that exposure to family planning messages on the radio is associated with increased modern contraception uptake ( 23 ) and knowledge ( 24 ). This finding suggests that the ABRI project's radio program played an integral role in raising family planning awareness and uptake in ABRI initiative areas.…”
Section: Discussionmentioning
confidence: 99%